Influence of Product, Price, Promotion and Place on Banana Market Trend in Kilimanjaro-Tanzania - Tumaini, Steven; Gwahula, Raphael; Macha, Salvio (European Scientific Journal, ESJ, 2024)
The study focuses on the influence of Product, Price, Promotion and Place on Banana Market trends in Kilimanjaro. Also, the study provides the market strategy to enhance the competitiveness of banana companies in the current market dynamics. Through quantitative research, this paper revealed the effectiveness of (4P) in the Banana marketing strategy and the significant links between place, price, products, promotion and the impact in increasing the market opportunity in the banana sector. Specifically, the study evaluates the performance of marketing strategy practices across various dimensions. The Marketing mix strategy was explored in terms of 4p. The study was conducted in Kilimanjaro targeting a sample of 575 banana growers from 52 wards. This study employed a cross-sectional survey approach to examine the Influence of Four (4P) in the banana value chain Kilimanjaro. Descriptive statistics and chi-square tests were used in data analysis and the results were presented in tables to underline the study’s important conclusion and recommendations. The results show that 99.3% of banana growers have a great challenge with access to the market and poor price information. Moreover, 62.8% of producers rely on middlemen rather than delivering bananas to private companies. Based on these findings, the private sectors are required to decentralize the business model and develop a marketing strategy by implementing the marketing mix in a way that will acquire and then sustain the competitive edge in the market. These will enhance the competitiveness of banana companies and lay a solid foundation for their sustainable success in the banana business.